2018
DOI: 10.3389/fpsyg.2018.00943
|View full text |Cite
|
Sign up to set email alerts
|

The Central Executive Mediates the Relationship Between Children’s Approximate Number System Acuity and Arithmetic Strategy Utilization in Computational Estimation

Abstract: Studies investigating the relationship between working memory (WM) and approximate number system (ANS) acuity in the area of arithmetic strategy utilization are scarce. The choice/no choice method paradigm was used in the present study to determine whether and how ANS acuity and WM components affected strategy utilization. The results showed that the central executive (CE) mediated the relationship between ANS acuity and strategy utilization. Furthermore, quantile regression analyses revealed that the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…On the one hand, they suggest that children who exhibited weaker mathematical reasoning also probably have limited calculation skills, which could explain a weaker relationship between both skills for the lower and intermediate quantiles as compared to the higher quantile. This explanation resembles the one proposed by Li et al, (2018) in reference to the approximate number system performance not being predictive of strategy choice in multiplication for the lower quantiles. Alternatively, Fuchs et al, (2020) propose that children who showed low and intermediate mathematical reasoning performance tend to approach word problems by adding the numbers presented on the problems, without engaging with mathematical reasoning.…”
Section: The Effects Of the Level Of Mathematical Reasoning On The Re...supporting
confidence: 71%
See 2 more Smart Citations
“…On the one hand, they suggest that children who exhibited weaker mathematical reasoning also probably have limited calculation skills, which could explain a weaker relationship between both skills for the lower and intermediate quantiles as compared to the higher quantile. This explanation resembles the one proposed by Li et al, (2018) in reference to the approximate number system performance not being predictive of strategy choice in multiplication for the lower quantiles. Alternatively, Fuchs et al, (2020) propose that children who showed low and intermediate mathematical reasoning performance tend to approach word problems by adding the numbers presented on the problems, without engaging with mathematical reasoning.…”
Section: The Effects Of the Level Of Mathematical Reasoning On The Re...supporting
confidence: 71%
“…However, statistical comparisons across quantiles are not reported. Furthermore, Li et al, (2018) found that approximate number system performance in fourth grade significantly predicted concurrent strategy choice on a double-digit multiplication task for median and high quantiles (50 th , 75 th and 85 th ), but not for lower performance (15 th and 25 th ), though statistical comparison between quantiles were not reported. Li et al, (2018) offer several possible interpretations for their findings.…”
Section: The Effects Of the Level Of Mathematical Reasoning On The Re...mentioning
confidence: 91%
See 1 more Smart Citation
“…Children chose the numerically greater collection well above chance; this suggests that while they may sometimes have been led astray by the numerically smaller collection having a larger total surface area, they could still succeed on a majority of trials. Some portion of the difference in performance across the stimulus sets could be due to the differing EF demands of the stimuli (Gilmore et al, 2013;Li et al, 2018 He, Zhou, Zhou, He, & Chen, 2015;Hollingsworth, Simmons, Coates, & Cross, 1991;Izard & Dehaene, 2008;Leibovich & Henik, 2013;Piazza, Izard, Pinel, Le Bihan, & Dehaene, 2004).…”
Section: Ans Training: Approximate Number Comparisonmentioning
confidence: 99%
“…While some studies suggest that executive functions (EF) might serve as the underlying link between better ANS performance and better school mathematics performance (Gilmore et al, 2013;Li et al, 2018), some recent work has found the opposite to be true (i.e., that ANS precision and number language or number knowledge survive as the only unique predictors of school math ability while EF are not unique (Malone et al, 2020(Malone et al, , 2019Purpura & Logan, 2015). This is an area that will benefit from additional exploration.…”
mentioning
confidence: 99%